ChemInform Abstract: Broensted Acid‐Catalyzed Cascade Reactions Involving 1, 2‐Indole Migration. Issue 4 (January 2016) - Alvarez, Estela; Nieto Faza, Olalla; Silva Lopez, Carlos; Fernandez‐Rodriguez, Manuel A.; Sanz, Roberto
Abstract: Various indole‐functionalized benzofulvene derivatives are obtained by a cascade reaction of indoles with propargylic diols involving an unusual metal‐free 1, 2‐indole migration onto an alkyne.